International Pediatric Otolaryngology Group (IPOG) consensus recommendations: Routine peri-operative pediatric tracheotomy care. (July 2016) - Strychowsky, Julie E.; Albert, David; Chan, Kenny; Cheng, Alan; Daniel, Sam J.; De Alarcon, Alessandro; Garabedian, Noel; Hart, Catherine; Hartnick, Christopher; Inglis, Andy; Jacobs, Ian; Kleinman, Monica E.; et al.
Abstract: Objectives: To develop consensus recommendations for peri-operative tracheotomy care in pediatric patients. Methods: Expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). The mission of the IPOG is to develop expertise-based consensus recommendations for the management of pediatric otolaryngologic disorders with the goal of improving patient care. The consensus recommendations herein represent the first publication by the group. Results: Consensus recommendations including pre-operative, intra-operative, and post-operative considerations, as well as sedation and nutrition management are described. These recommendations are based on the collective opinion of the IPOG members and are targeted to (i) otolaryngologists who perform tracheotomies on pediatric patients, (ii) intensivists who are involved in the shared-care of these patients, and (iii) allied health professionals. Conclusion: Pediatric peri-operative tracheotomy care consensus recommendations are aimed at improving patient-centered care in this patient population.